A investida neoliberal na América Latina e as novas determinações da dependência - Amaral, Marisa Silva (2006)
The dependence, according to Marxist dependence s theory, can be understood as a conditioning situation from which development of the central economies occurs at the costs of the underdevelopment of the peripheral economies, this fact marked by the intensification of the process of transfer values produced in periphery and accumulated in the center s countries. It causes needs that, in the periphery, mechanisms of labor superexplotation are exacerbated as way to continue its internal process of capital accumulation. The aim of this study is to demonstrate that, in the marks of the current capitalism marked by gain of neoliberal hegemony perspective and for the constitution of a new Latin-American pattern exporter , the dependence is established trough an intense invigoration of the structural external vulnerability from peripheral countries, combined with a situation of intense financial fragility, both like in the immediate result of the excessive commercial and financial openess, lack of mobility capitals control and also of the insertion s type of Latin-American economies, in whose line of exportations prevails commodities and/or industrial products with low added value. Thus, we have that the neoliberalism is presented as a historical current form of dependence, the external vulnerability appears as characteristic of dependence, which is exacerbated in the new historical form, and as a result, the possibilities of capitalist development are put in the periphery through the workforce superexplotation.